Is Group Choice a Part of Economics?: Reply - Allin, Bushrod W. (Quarterly Journal of Economics, 1953)
Is Group Choice a Part of Economics? Reply Get access Bushrod W. Allin Bushrod W. Allin Bureau of Agricultural Economics, Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 67, Issue 4, November 1953, Pages 613–614, https://doi.org/10.2307/1883607 Published: 01 November 1953